A political economy of press self-regulation: the case of South Africa. - Duncan, Jane (Media, Culture & Society, 2014)
In 2011, the Press Freedom Commission (PFC) was established to recommend the most appropriate regulatory form for South Africa’s press, in the wake of the ruling African National Congress’s (ANC) criticism of the existing system of self-regulation as toothless and self-serving. The ANC has argued for the establishment of a statutory Media Appeals Tribunal. South Africa is not the only country having these debates. In the wake of the phone hacking scandal in Britain, an enquiry chaired by Lord Justice Leveson also considered alternative regulatory forms to self-regulation, given the failure of the Press Complaints Commission to stem the ethical excesses of the tabloid press. Several Southern African governments either have instituted or are considering instituting statutory regulation, and politicians are wasting no time in capitalizing on developments in Britain to drive a press control agenda. This article considers the merits of arguments for and against press self-regulation in South Africa, and options for the future. Using a political economy analysis, it argues that while the system has proved to be very effective in monitoring and adjudicating ethical breaches, it has been implicitly designed to cause minimal offence to the industry, and recent reforms have only partly addressed the problem.